2016
DOI: 10.3847/0004-637x/827/2/127
|View full text |Cite
|
Sign up to set email alerts
|

ASASSN-14li: A MODEL TIDAL DISRUPTION EVENT

Abstract: ASASSN-14li is a recently discovered tidal disruption event with an exceptionally rich data set: spectra and lightcurves in soft X-rays, UV, optical, and radio. To understand its emission properties in all these bands, we have extended our model for post-tidal disruption accretion and photon production to estimate both soft X-ray radiation produced by the "prompt" accretion phase and synchrotron emission associated with the bow shock driven through an external medium by the unbound tidal debris, as well as opt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
150
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(161 citation statements)
references
References 47 publications
8
150
3
Order By: Relevance
“…In their model, the post-peak optical luminosity naturally decays ∝ t −5/3 because it is directly associated with mass fall-back, and the emerging radiation has the observed low luminosity, low temperature, and large radial scale. Applied to the best observed TDE so far, ASSASN-14li (Holoien et al 2016a), this model agrees nicely with all observed optical and UV features (Krolik et al 2016).…”
Section: Introductionsupporting
confidence: 82%
“…In their model, the post-peak optical luminosity naturally decays ∝ t −5/3 because it is directly associated with mass fall-back, and the emerging radiation has the observed low luminosity, low temperature, and large radial scale. Applied to the best observed TDE so far, ASSASN-14li (Holoien et al 2016a), this model agrees nicely with all observed optical and UV features (Krolik et al 2016).…”
Section: Introductionsupporting
confidence: 82%
“…The total energy we infer corresponds to a very small amount of material (∼2×10 −5 M e for the 0.2 steradians case), while the total mass of the unbound material is orders of magnitude larger for the disruption of a solar mass or even 0.1 solar mass star. Even if we assume that only the fastest-moving tail of the distribution of unbound debris produces the radio emission, as recently suggested by Krolik et al (2016), the emission expected in this case would still require a density tens to hundreds of times higher than the density we compute to match our observed fluxes. While the density we derive by assuming perfect equipartition is, like the energy, a lower limit, it is difficult to explain such a large discrepancy.…”
Section: Radio Emission From the Unbound Debrismentioning
confidence: 65%
“…evolution. While the rate of material returning to pericenter is frequently invoked to explain the luminosity evolution of TDEs, given the complexity of the physical processes involved (Kochanek 1994;Guillochon & Ramirez-Ruiz 2013;Guillochon, Manukian & Ramirez-Ruiz 2014;Metzger & Stone 2016;Krolik et al 2016), it is likely that the rate of material returning to pericenter has limited bearing on the overall luminosity evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast with ASASSN-14ae, in which the He ii λ4686 line became stronger relative to the Balmer lines as the event progressed (Brown et al 2016). Unlike the two other ASASSN TDEs, ASASSN-14li showed strong X-ray emission, and, due to it's proximity, was the target of several groundbased (Alexander et al 2016;van Velzen et al 2016;Romero-Cañizales et al 2016), space-based (Miller et al 2015;Cenko et al 2016;Peng, Tang & Wang 2016;Jiang et al 2016), and theoretical efforts (Krolik et al 2016;Kochanek 2016a).…”
Section: Introductionmentioning
confidence: 99%